Comparison Of Applying Single Index Model And Capital Asset Pricing Model By Means Achieving Optimal Portfolio - Siti Chanifah; Hamdani Hamdani; Andi Gunawan (Agregat: Jurnal Ekonomi dan Bisnis, 2020)
The aim of this research is to analyse the comparison of applying Single Index Model and Capital Asset Pricing Model by means of achieving the Optimal Portfolio towards registered Issuers which are listed on the Liquid Index 45 (LQ45). The observation has been conducted for 60 months, since February 2014 until January 2019. Quantitative approach has been used to analyse 45 companies as the total number of population of the research. There have been chosen 26 companies (issuers) as the sample of the research through Purposive Sampling Technique out of 45 companies. Single Index Model and CAPM have been used as the tools of analysis in this research. The results of the research show that portfolio is formed by Single Index Model because it considers all aspects of the economy which cause a security which may avoid from losses. Meanwhile, Capital Asset Pricing Model only considers particular risk in an efficient portfolio combinations. Needless to say, it would be better for investors to use Single Index Model in order to gain the most valueable achievement on investment yield value.